Does Self Efficacy Plays A Vital Role In Academic Achievement? - K. Vijayalakshmi, Dr. M. Selvarani (International Journal of Advanced Science and Technology, 2020)
This article focuses on how factors of self efficacy influence student’s academic achievement. Self efficacy theory, Social cognitive theory are discussed. Self efficacy measurement scales are described. The student’s self   efficacy level is discussed. To improve self efficacy, teachers, student environment and educational institutions must contribute to nurture Student’s self efficacy. This article concludes for student’s academic achievement, self efficacy is essential.